2022
DOI: 10.1186/s12905-022-01669-2
|View full text |Cite
|
Sign up to set email alerts
|

Women survivors of intimate partner violence talk about using e-health during pregnancy: a focus group study

Abstract: Background Pregnancy is a period of particular vulnerability to experience intimate partner violence against women (IPVAW). eHealth strategies have been implemented to identify women exposed to IPVAW and to combat the abuse and empower them, but there is a lack of evidence on the use of these strategies among pregnant women. This work aims to identify the needs, concerns and preferences of survivors about the use of eHealth strategies to counsel and empower pregnant victims of IPVAW in antenata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…This includes information on the definition and different forms of IPV, danger assessment, information on related topics (e.g., legal advice, finances and housing) and step-by-step instructions for preparing a separation [ 44 , 65 68 ]. However, consistent with previous research, we found that these contents can be overwhelming and exacerbate the experienced distress and social isolation [ 44 , 66 , 69 ], if not accompanied by ongoing psychological support. Therefore, digital interventions should ideally serve as a bridge to face-to-face services, that can provide this support [ 44 , 66 , 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…This includes information on the definition and different forms of IPV, danger assessment, information on related topics (e.g., legal advice, finances and housing) and step-by-step instructions for preparing a separation [ 44 , 65 68 ]. However, consistent with previous research, we found that these contents can be overwhelming and exacerbate the experienced distress and social isolation [ 44 , 66 , 69 ], if not accompanied by ongoing psychological support. Therefore, digital interventions should ideally serve as a bridge to face-to-face services, that can provide this support [ 44 , 66 , 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…If they perceive it like this, they may not want to be randomized into control group or they may drop out after been randomized to usual care instead of intervention. To overcome this difficulty with acceptance of allocation to the control group, we followed the input of IPV survivors in a focus group we conducted [13]. Amongst other things the survivors informed us that they would prefer delayed intervention instead of usual care in a control group.…”
Section: Discussionmentioning
confidence: 99%
“…eHealth interventions have the potential to provide more flexibility and safer spaces than face-to-face interventions, making it particularly useful for screening violence, empowering women and reducing exposure to IPV [12]. IPV survivors considered appropriate and necessary to be screened using eHealth strategies in antenatal care settings and perceived that video counselling is a viable and acceptable tool for pregnant women who experience IPV [13]. Trials have shown that e-health screening tools are effective in getting women to disclose or detect IPV [14][15][16].…”
Section: Background and Rationalementioning
confidence: 99%
“…According to Myers' recommendations (1998) for conducting focus groups, seven PCPs were selected via incidental sampling to participate. In this sense, previous studies (Fernández et al, 2022;Nyumba et al, 2018) support the use of a single focus group to conduct research.…”
Section: Participantsmentioning
confidence: 94%